PENERAPAN WAKAF DI KANIGORO BLITAR (Studi Atas Pelaksanaan PP No. 28 Tahun 1977 dan UU No. 41 Tahun 2004) - Fatoni, Achmad (Fakultas Syariah, 2011)
This research examines the application of waqf in Kanigoro Blitar Sub-district based on regulation 28/1977 and after the enactment of Law No. 41/2004 on the application of Endowments and inhibiting factor endowments moving objects in accordance with Law No. 41/2004 on Endowments. The study concluded that the implementation of waqf in Kanigoro Â before the enactment of Law no. 41 Year 2004 on endowments, namely the enactment of PP. 28 of 1977 can be applied in the field, both in terms of implementation of the procurement or obeying the rules which in this case is the rule registering legally the land. However, related to the enactment of Law No.. 41 Year 2004 regarding waqf endowments, especially on moving objects has not been effective at all. Penelitian ini mengkaji tentang penerapan wakaf di kec. Kanigoro sesuai dengan PP 28/1977 dan sesudah berlakunya UU no 41/2004 tentang Wakaf dan faktor penghambat penerapan wakaf benda bergerak sesuai UU no 41/2004 tentang Wakaf. Penelitian menyimpulkan bahwa penerapan wakaf pada masyarakat di Kec. Kanigoro Kab. Blitar sebelum berlakunya UU No. 41 Tahun 2004 tentang wakaf, yaitu pada berlakunya PP No. 28 Tahun 1977 bisa diterapkan di lapangan, baik dalam pelaksanaan pengadaannya ataupun dari segi mentaati aturannya yang dalam hal ini adalah aturan mensertifikatkan tanahnya. Namun berkaitan dengan berlakunya UU No. 41 Tahun 2004 tentang wakaf khususnya pada wakaf benda bergerak belum efektif sama sekali Â